Study of short circuit characteristic and fault current contribution of generator - Foo, Clement Ji Wang (2017)
DC shipboard distribution systems is an emerging technology that have recently gained spotlight. The main advantage of DC shipboard distrbution system is improved fuel efficiency in the desired operational region. However, DC shipboard distribution system have their major shortfall due to the inadequency of comprehensive protection system. The generation system of a typical DC shipboard power system comprises of generator interfaced with voltage source converter which consists of freewheeling diodes and are susceptible to damage during fault. The fault current supplied by the synchronous generator during the fault is responsible for damage of freewheeling diodes. This report presents analysis of fault currents supplied by the synchronous generator during the three phase fault. Various de-excitation systems have been implemented to study the effect on the fault currents.